Dental workforce development as part of the oral health agenda for Brunei Darussalam. (24th January 2013) - Wilson, Nairn H. F.; Shamshir, Z. Abidin; Moris, Sylviana; Slater, Mabel; Kok, Ei Chuen; Dunne, Stephen M.; Said, Samsiah H. M.; Lee, James M. K.; Gallagher, Jennifer E.
<x xml:space="preserve">Abstract</x> Background Brunei Darussalam is a Sultanate with a Malay Islamic monarchy. There are high levels of dental disease among its 406, 200 population. The population's oral health needs require an integrated blend of primary and specialist care, together with oral health promotion. Process and outcomes This paper describes the planning and measures taken to address these needs. In accordance with an oral health agenda published and launched in 2008, focusing on access, health promotion and prevention, and the education and training of the dental workforce, the Brunei Darussalam Ministry of Health is seeking to improve oral health status and reduce the burden of oral disease. It also seeks to transform the country's oral health services into a preventatively orientated, high‐quality, seamless service underpinned by the concept of 'teeth for life'. In the process of effecting this transition, the Brunei Darussalam Ministry of Health is developing a dental workforce fit for future purpose, with an emphasis on a modern approach to skill mix. An important element of this programme has been the development of a highly successful Brunei Darussalam Diploma in Dental Therapy and Dental Hygiene. Conclusion It is concluded that the Brunei Darussalam oral health agenda and, in particular, the forward‐looking programme of dental workforce development is a model for other countries facing similar oral health challenges.